Respuestas
Respuesta dada por:
1
1) 3x + 2y = 0 (5)
2) 2x + 5y = 11 (-2)
15x + 10y = 0
- 4x - 10y = - 22
-------------------------
11x + 0y = - 22
11x = - 22
x = - 22/11
x = - 2
Reemplazo el valor de x en 1
3x + 2y = 0
3 (- 2) + 2y = 0
- 6 + 2y = 0
2y = 6
y = 6/2
y = 3
x = - 2
y = 3
2) 2x + 5y = 11 (-2)
15x + 10y = 0
- 4x - 10y = - 22
-------------------------
11x + 0y = - 22
11x = - 22
x = - 22/11
x = - 2
Reemplazo el valor de x en 1
3x + 2y = 0
3 (- 2) + 2y = 0
- 6 + 2y = 0
2y = 6
y = 6/2
y = 3
x = - 2
y = 3
Respuesta dada por:
0
Respuesta:
Explicación paso a paso:
1) 3x + 2y = 0 (5)
2) 2x + 5y = 11 (-2)
15x + 10y = 0
- 4x - 10y = - 22
-------------------------
11x + 0y = - 22
11x = - 22
x = - 22/11
x = - 2
Reemplazo el valor de x en 1
3x + 2y = 0
3 (- 2) + 2y = 0
- 6 + 2y = 0
2y = 6
y = 6/2
y = 3
x = - 2
y = 3
Preguntas similares
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 10 años
hace 10 años